Global best practices in film archives management and services: lesson for Nigeria (2014)
Vital information resources required for education, enlightenment and decision-making are contained in films. In view of its composition and chemical make-up, film as an information container requires special care and attention if the information residing in it is to endure for a long time to serve its purpose. There exist international best practices in the management of film which have been developed over the years. This paper makes an exploration of the global standards in film preservation, paying particular attention to the efforts of film archives and organizations around the world in setting standards for film management. These standards are considered in key areas of film management like film handling, storage, cataloguing and access. Finally, the paper enjoins developing countries like Nigeria to avail themselves of these global standards in film management in order to ensure the survival of information resources in film format.